Accessing the academy: developing strategies to engage and retain marginalised young people on successful educational pathways - Mannay, Dawn (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryFor young, non-traditional students, higher education pathways are often characterised by initial aspirations and later disappointments when classed, gendered and relational positionings conflict with students’ identities and contribute to their withdrawal from academia. This paper discusses an innovative ‘group encounter’ that engendered an opportunity for young marginalised students to gain access to a successful learner identity creating inclusive spaces in place of divided communities. The central argument of the paper is that if we intend not only to widen access at points of entry but rather engender a space where academic journeys can be successfully completed and projects of social mobility achieved, there is a need to create inclusive spaces for young people in place of divided communities.Key words: affinity space, higher education, inequality, youth, marginalisation.